JAVANESE CULTURAL WORDS IN LOCAL NEWSPAPERS IN CENTRAL JAVA AS A LANGUAGE MAINTENANCE MODEL - Deli Nirmala (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2015)
Javanese cultural words are the linguistic units which are very specific to Javanese culture and society. This article aims at describing what Javanese cultural words that are found in the local newspapers, what they represent, and why they are used in the local newspapers in Central Java. Non-participant observation is used to present the data for analysis, continued with page-filing and note-taking techniques. Referential, reflective-introspective, and abductive inferential methods are used to analyze the data. The result indicates that the Javanese cultural words found in the local newspapers represent festivals, rituals, Javanese ways of life, social activities, actions, feelings, thoughts, behavior, and experiences. The words become the indicators that the journalists of the local newspapers in Cental Java have positive attitudes toward Javanese words. This becomes a model for language maintenance of Javanese. This implies that the words are stored in the long-term memory, that become mental image, which are used when needed by the user for communication. The existence of the concepts residing in the mind will make the Javanese language maintenance possible, which is supported by the attitudes of the Javanese.